RESPIRATORY ADAPTATION AND PULMONARY FUNCTION PARAMETERS IN COMPETITIVE SWIMMERS: A SYSTEMATIC REVIEW OF PHYSIOLOGICAL MECHANISMS AND ENVIRONMENTAL FACTORS - Anna Gwizdek; Dawid Szczepański; Sebastian Konecki; Natalia Bylak; Grzegorz Jałoszyński; Oliwia Marciniak; Bruno Makowski; Maria Kurt; Norbert Gromadzki; Marcin Patryk Barbachowski (International Journal of Innovative Technologies in Social Science, 2026)
Research Objectives: Competitive swimming uniquely impacts the respiratory system, inducing profound physiological adaptations and environmental risks. This systematic review synthesizes current evidence on pulmonary function, adaptation mechanisms, and airway dysfunction etiology in swimmers. Methods: A systematic search was conducted up to February 2026. Peer-reviewed studies assessing objective lung function, respiratory mechanics, and environmental exposures in aquatic athletes were included. Data underwent narrative synthesis due to methodological heterogeneity. Key Findings: The aquatic environment acts as a potent respiratory stimulus. Elite swimmers consistently exhibit supranormal lung volumes (FVC, TLC) and diffusion capacity (DLCO), driven by isotropic growth and alveolar hyperplasia. However, this is counterbalanced by the "swimmer’s paradox". Chronic inhalation of disinfection by-products (e.g., trichloramine) combined with massive ventilatory demands induces epithelial damage and oxidative stress, resulting in a high prevalence of exercise-induced bronchoconstriction (EIB) and non-allergic airway hyperresponsiveness. Conclusions: The impact of swimming on respiratory health appears to be dose-dependent. While structured training is associated with enhanced pulmonary development, high-intensity exposure in chlorinated environments may increase the risk of adverse respiratory effects. Protecting athletes requires sport-specific diagnostic strategies and optimized ventilation systems in aquatic facilities.